Application of Food-Grade Proteolytic Enzyme for the Hydrolysis of Regenerated Silk Fibroin from Bombyx mori - Ji An Joung; Mi Na Park; Ji Young You; Bong Joon Song; Joon Ho Choi (Journal of Chemistry)
In vitro biodegradation of Bombyx mori silk fibroin (SF) was studied using food-grade proteolytic enzymes to replace acid hydrolysis. Based on the residual protein quantity and yield of amino acids (AAs) after enzymatic hydrolysis, we evaluated the proteolytic enzyme process of SF. FoodPro and Alcalase that are classified as alkaline proteases are selected as two of the best candidate enzymes for hydrolysis of SF. The activity of these enzymes exhibits a broad range of pH (6.5 to 9.0) and temperature (50°C to 65°C). The single enzyme treatment of SF using FoodPro exhibited a hydrolytic efficiency of 20–25%, and >2 g/L AAs were released after reaction for 3 h. A 2-stage enzymatic treatment using a combination of FoodPro and Flavourzyme in a sequence for a reaction time of 6 h was developed to enhance the efficiency of the proteolytic process. The yield of AAs and residual protein quantity in the enzymatic hydrolysates obtained from FoodPro-treated regenerated SF in the 1st step was 2,040 ± 23.7 mg/L and 70.6%, respectively. The yield of AAs was > two-fold (4,519 ± 42.1 mg/L), whereas the residual protein quantity decreased to 55.1% after the Flavourzyme treatment (2nd step) compared to those of the single FoodPro treatment. In the mixed treatment by simultaneously using FoodPro and Flavourzyme, approximately 45% of SF was degraded and 4.5 g/L of AAs were released within 3 h of reaction time. The regenerated SF and its enzymatic hydrolysates were characterized by performing UV-visible spectra, gel electrophoresis, and size-exclusion chromatography analyses. In the 2-stage treatment using FoodPro initially and subsequently Flavourzyme, the aggregates and high molecular weight proteins of SF were dissociated and degraded into the low molecular weight proteins/peptides (10–15 kDa and 27 kDa). SF hydrolysates as functional food might be enzymatically produced using the commercial food-grade proteolytic enzymes.